A new species of Pseudolagarobasidium from Brazil and new insights on Cerrena (Basidiomycota, Cerrenaceae) - Westphalen, Mauro C.; Motato-Vásquez, Viviana (Phytotaxa, 2022)
In this study, Pseudolagarobasidium pallens sp. nov. is proposed based on morphological and phylogenetic studies. Specimens were collected in Brazil and used for DNA sequence analyses of the internal transcribed spacer and the large subunit of the nuclear ribosomal RNA gene. The basidiomes of P. pallens are characterized by a pale cream coloration when fresh, hydnoid hymenophore with long teeth and thin whitish context. Microscopically, it differs from other related species by the larger basidiospores (4.6–)4.9–6.4(–6.8) × 3.2–4.5 µm. Phylogenetically, it is closely related to P. belizense. We also provide sequences of the Brazilian species Cerrena cystidiata for the first time and confirm that is closely related to the generic type C. unicolor. A taxonomic key to all species currently accepted in Pseudolagarobasidium and a brief discussion on the family Cerrenaceae as well as a comparison table of all its genera are also presented.